Gratitude as a Christian lifestyle: An Afro-reformed theological perspective - Manala, Matsobane J. (HTS teologiese studies, 2018)
31 October 2017 marked the 500th anniversary of the birth of the Reformation in Germany, West Europe. One of the most important legacies of the Reformation is the teaching concerning God’s gracious salvation, received and appropriated only through faith in Christ Jesus our Saviour. The current article seeks to focus on reflection on gratitude as a Christian lifestyle in response to God’s redemption. The article reflects on gratitude as recognition account, highlighting the importance of gratitude as a Christian virtue, as a socioreligious phenomenon, and its importance in human happiness and well-being. This, as it shaped the life of Christians, is found especially in the African continent, in whose traditional life, gratitude was ubiquitous, known and practised even before conversion to the Protestant religion. The article also briefly highlights the fact that a relaxed attitude regarding the teaching on gratitude could result in Sunday or nominal Christianity and the demise of prophetic Christianity. Some concluding thoughts regarding gratitude are shared.